2014
DOI: 10.1068/c10204
|View full text |Cite
|
Sign up to set email alerts
|

Policy Transformations and Translations: Lessons for Sustainable Water Management in Peri-Urban Delhi, India

Abstract: Citation: Randhawa, Pritpal, and Fiona Marshall. "Policy transformations and translations: lessons for sustainable water management in peri-urban Delhi, India." Environment and Planning C: Government and Policy 32.1 (2014): 93-107.Official URL: http://www.envplan.com/abstract.cgi?id=c10204More details/abstract: This paper explores the complex interactions that occur as formal policies are interpreted and utilised to develop water management plans in peri-urban Delhi. With an emphasis on people's participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…'Implementation deficits' have also been identified outside public procurement in areas including climate protection (Jordan, 1999;Krause, 2011;Pitt, 2010), waste management (Nilsson et al, 2009) and rural planning (Gilg and Kelly, 1997). Most recently, Randhawa and Marshall's (2014) case study of an Indian water management project demonstrated how implementation practices often end up bearing little resemblance to what is contained in government action plans. Evidently, there is nothing inevitable about policy translating into practice, whether in procurement or in any other domain.…”
Section: Introductionmentioning
confidence: 99%
“…'Implementation deficits' have also been identified outside public procurement in areas including climate protection (Jordan, 1999;Krause, 2011;Pitt, 2010), waste management (Nilsson et al, 2009) and rural planning (Gilg and Kelly, 1997). Most recently, Randhawa and Marshall's (2014) case study of an Indian water management project demonstrated how implementation practices often end up bearing little resemblance to what is contained in government action plans. Evidently, there is nothing inevitable about policy translating into practice, whether in procurement or in any other domain.…”
Section: Introductionmentioning
confidence: 99%
“…It includes a diversity of urban and peri-urban settlements, with people variously accommodated in villages, unauthorized colonies, slums, and middle-class colonies. This area has been enormously affected by the transformations in nearby Delhi—for example, through the loss of farmland to urban development and through the relocation of polluting industries from Delhi to Ghaziabad [26,27]. The population in Ghaziabad has grown as people are attracted by its urbanizing nature, including rural migrants looking for work and urban populations relocating because of cheaper housing and improved commuting possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…The result has been a lowering of the water table. Areas such as Karhera have been affected by these urbanization processes, and their tubewells no longer provide adequate sources of water [3,26]. Water shortages have also reduced the amount of land suitable for cultivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leach 2008;Leach et al 2010b), others pick bits and pieces in combination with other theories, for example resilience (Thapa et al 2010), conflict transformation theory (Rodriguez et al 2013) or livelihood studies (Muller-Mahn et al 2010). Ely et al (2013Ely et al ( , 2014) focus on 'innovation pathways' and the idea of 'opening up' and 'broadening out', and Randhawa and Marshall (2014) explore how the institutional context prioritises particular pathways to sustainability in an Indian water management context. However, it is hard to find research that address all components (narratives, actors, their ideas/perceptions, Pathways and the governance/institutional context) in ways that are systematic enough to reveal the mechanisms of domination and suppression of alternative Pathways.…”
Section: )mentioning
confidence: 99%